A cross-country comparison of gender differences in job-related training: The role of working hours and the household context - Christina Boll; Elisabeth Bublitz (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2016)
Regarding gender differences, theory suggests that in a partnership the individual with the lower working hours and earnings position should exhibit lower training participation rates. Since women are more likely to match this description, we investigate whether systematic group differences explain gender variation. Across all countries, male workers are not affected by their earnings position. For female workers in Germany, but not Italy or the Netherlands, working part-time instead of full-time corresponds with a decrease in course length by 5.5 hours. Also, regarding German parttime employed women, single earners train 5.6 hours more than secondary earners. The findings of our study hold at the extensive and the intensive margin, suggesting that Germany faces particular household-related obstacles regarding gender differences in job-related training.
Keywords: J16; J24; M53; 330; further education and training; gender differences; country comparisons